CONTINUITY OF CARE MANAGEMENT IN NY. R WITH RUPTURE OF THE PERINEUM DEGREE I AT PMB MIDWIFE WANTI MEDAN CITY - Marselina; Ribur Sinaga; Ingka Pangaribuan; Veronika Manalu; Reni Elisabet Sihotang; Eflora Kariana Br Sembiring; Sri Muliana Putri Bakara (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Rupture of the perineum is a common complication in childbirth that can increase the risk of infection and postpartum maternal morbidity. Rupture of the perineum occurs due to maternal factors (parity, birth distance, and infant weight), improper delivery and past labor history. Rupture of the perineum has its own impact on the mother which is one of the causes of complications during the postpartum period until death. This study aims to describe the continuity of care (COC) in Mrs. R who experienced a perineal rupture of the first degree at PMB Midwife Wanti, Medan Deli District. A healthy Indonesia is one of the targets for social transformation for the 2045 golden program, which is Indonesia’s goal to become a developed, sovereign, and sustainable country by 2045, improving quality. There are 60% of cases of mothers giving birth experiencing perineal tears which result in bleeding and infectionsafter childbirth, while in Indonesia out of 26 million mothers giving birth, 40% of mothers experience rupture perineumThe research was conducted through a case study approach with service stages that include pregnancy, childbirth, postpartum period, newborn (BBL), and family planning (KB). This type of research is qualitative descriptive through a case study approach. The subject of the study was Mrs. R, a primigravida mother who underwent care from pregnancy to birth control at PMB Wanti. Data was collected through interviews, observations, physical examinations, and SOAP documentation. The intervention was structured based on Varney’s seven-step midwifery care management. The results show that the systematic implementation of COC care can improve the quality of services and accelerate the recovery of postpartum mothers. Evidence-based interventions such as personal hygiene, nutrition education, and psychological support have been shown to be effective in supporting the healing of perineal wounds and maternal readiness during postpartum and breastfeeding.